1-Rock-Bursts at the Teck-Hughes Mine - J. D. Christian (Canadian Institute of Mining, Metallurgy and Petroleum, 1939)
WHEN mining development began in the Kirkland Lake camp, twenty-five years ago, there was very little information obtainable from surface showings as to the nature of the ore deposits. A length of almost a mile of the main 'break' lay under the south arm of the lake, and elsewhere most of the outcrops were covered with glacial drift. Shafts were sunk on ore-bodies of uncertain value, either on the outcrop of the veins or-because of the lake to the north-in the south or hanging-wall. In the second year of the camp's development, the Great War broke out and retarded progress for its duration. He would have been a real optimist who, in those early years, could have foreseen mining at depths of more than a mile.